Adsorptive removal of nitrate Ions from aqueous solutions using acid treated sunflower seed husk (Helianthus annuus) - Moyo, Mambo; Maringe, A.; Chigondo, Fidelis; Nyamunda, Benias C.; Shumba, Munyaradzi (2016)
The ability to convert a waste by-product, sunflower seed husk (Helianthus annuus), into an economically cheap adsorbent has been investigated for nitrate removal from aqueous solution through sorption studies. The sunflower seed husk was characterized by physisorption, Brunauer Emmet Teller (BET). Fourier transform Infrared (FTIR) were recorded before and after adsorption to explore the number and position of the functional groups available for nitrate binding on to the studied adsorbent. Optimum adsorption conditions for nitrate removal were determined as a function of pH, adsorbent dosage and contact time. The sorption capacity decreased with increasing sorbent dosage. The optimum contact time was 120 min, optimum biomass dose was 3.0 g and the optimum pH for nitrate removal was 2.0. The adsorption data conformed to both the Langmuir and the Freundlich isotherms but fitted best into the Langmuir model. The R 2 for Langmuir equation was 0.9940 and that for Freundlich was 0.8190. The study demonstrated the efficacy of disposed sunflower seed husk as efficient adsorbent material for the removal of nitrate ions from aqueous solution.